Compounds of Anthostomella brabeji, an endophytic fungus isolated from Paepalanthus planifolius (Eriocaulaceae) - De Amorim, Marcelo R. [UNESP]; Somensi, Andressa [UNESP]; Araujo, Angela R. [UNESP]; Bonifácio, Bruna V. [UNESP]; Bauab, Tais M. [UNESP]; Santos, Lourdes C. Dos [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2016)
In this study, fifteen endophytic fungi were isolated from Paepalanthus planifolius (Eriocaulaceae). From the capitula, seven endophytes were screened and evaluated for their metabolomic profile and radical scavenging activity (2,2-diphenyl-1-picrylhydrazyl (DPPH) assay). Chemical investigation of ethyl acetate extract of the endophytic fungus Anthostomella brabeji resulted in the isolation of one new compound, (+)-(6R∗,7S∗,8R∗)-6,7,8-trihydroxy-2,2-dimethyl-5,6,7,8-tetrahydro-chroman-4-one, and three known compounds: 6-hydroxy-2,2-dimethyl-5,6,7,8-tetrahydro-7,8-epoxycroman-4-one, siccayne and eutypinol. All of the compound structures were elucidated using 1D and 2D nuclear magnetic resonance (NMR) and mass spectrometry (MS) analyses. The antimicrobial activity of the compounds and A. brabeji extract were assayed against the microorganisms Staphylococcus aureus, Escherichia coli, Salmonella setubal and Candida albicans. Measured minimal inhibitory concentration (MIC) values ranged from 31.25 to 1000.0 μg mL-1.
Keywords: Anthostomella brabeji; Antimicrobial activity; Endophytic fungus; Paepalanthus planifolius